Kualitas Lada (Piper nigrum L.) Malonan 1 Terhadap Penggantian Air Perendaman - Dicky Aditya Warman; Nur Rizqi Bariroh; Dhyani Nastiti Purwantiningdyah (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
East Kalimantan is a province famous for its white pepper production. Post-harvest handling of white pepper at the East Kalimantan farmer level is by soaking pepper seeds in small rivers. The problem is the lack of small rivers in East Kalimantan and usually the water conditions in the rivers are not clean. One solution offered is to soak white pepper seeds by replacing the soaking water. This research was conducted at the East Kalimantan BPSIP testing laboratory in May 2023. The research design used was a Completely Randomized Design (CRD), 6 treatments 3 replications, where P0 = no water replacement, P1 = water replacement every 24 hours, P2 = water replacement 48 hours, P3 = water replacement every 72 hours, P4 = water replacement every 96 hours, P5 = water replacement every 144 hours. The results showed that replacing the soaking water every 48 hours gave the best results for water content (P <0.05%) which was 12.26%. Meanwhile, the results of the light seed content test with water replacement treatment every 96 hours showed the best results, namely 0.46% (P <0.05). In the foreign matter content test, the results were 0.40% to 1.49% and in the blackish pepper content test, the results were 0.61% to 1.59%. Meanwhile, the color test showed that replacing the soaking water gave better white pepper results compared to the treatment without replacing the soaking water. The study showed that replacing the soaking water produced white pepper quality according to quality I and II in SNI 0004:2013.